Production of p-hydroxyhydrocinnamic acid from tyrosine by Peptostreptococcus anaerobius. - Lambert, M A (1980)
Peptostreptococcus anaerobius was found to metabolize tyrosine to p-hydroxyhydrocinnamic acid [3-(p-hydroxyphenyl)propionic acid]. This acid was detected in spent growth media by gas-liquid chromatography, and its identity was confirmed by mass spectrometry.